Fifty shades darker [videorecording (DVD)] - Johnson, Dakota, 1989-; Dornan, Jamie, 1982-; Johnson, Eric, 1979-; Mumford, Eloise; James, E. L. (Universal Pictures Home Entertainment, 2017)
Anastasia has broken off her relationship with the troubled Christian to pursue a new career in a Seattle publishing house. While Christian wrestles with his inner demons, Anastasia must confront the anger and envy of the women who came before her.